THE INFLUENCE OF LEADERSHIP BEHAVIOR AND LEADERSHIP COMMUNICATION ON EMPLOYEE PERFORMANCE, MEDIATED BY EMPLOYEE ENGAGEMENT - Lovella Hexaratih Bassar; Singmin Johanes Lo (Dinasti Publisher, 2022)
This research analyzes the phenomena that occur to the decrease in employee performance result. To achieve the company's vision in its development requires employees who provide the best performance and contribute to building the company. This research aims to analyze the effect of leadership behavior and leadership communication on employee performance mediated by employee engagement at the Customer Relations and Administration Division of PT XYZ. This research uses a quantitative approach. The population in this research as many as 83 employees with the sampling technique used is a saturated sample so that all populations are used as respondents. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of research show that leadership behavior has a positive but not significant effect on employee performance, as well as on employee engagement. Employeee engagement does not mediate leadership behavior on employee performance. Leadership communication has a positive and significant effect on employee engagement, but has no significant effect on employee performance. Employee engagement has a positive and significant effect on employee performance, and succeeded in fully mediating leadership communication on employee performance.